Cardiopulmonary Response to Exercise in COPD and Overweight Patients: Relationship between Unloaded Cycling and Maximal Oxygen Uptake Profiles. (19th March 2015) - Ba, Abdoulaye; Brégeon, Fabienne; Delliaux, Stéphane; Cissé, Fallou; Samb, Abdoulaye; Jammes, Yves
Abstract : Cardiopulmonary response to unloaded cycling may be related to higher workloads. This was assessed in male subjects: 18 healthy sedentary subjects (controls), 14 hypoxemic patients with chronic obstructive pulmonary disease (COPD), and 31 overweight individuals (twelve were hypoxemic). They underwent an incremental exercise up to the maximal oxygen uptake (VO2 max), preceded by a 2 min unloaded cycling period. Oxygen uptake (VO2 ), heart rate (HR), minute ventilation (VE), and respiratory frequency (fR) were averaged every 10 s. At the end of unloaded cycling period, HR increase was significantly accentuated in COPD and hypoxemic overweight subjects (resp., + 14 ± 2 and + 13 ± 1.5  min −1, compared to + 7.5 ± 1.5  min −1 in normoxemic overweight subjects and + 8 ± 1.8  min −1 in controls). The fR increase was accentuated in all overweight subjects (hypoxemic: + 4.5 ± 0.8 ; normoxemic: + 3.9 ± 0.7  min −1 ) compared to controls (+ 2.5 ± 0.8  min −1 ) and COPDs (+ 2.0 ± 0.7  min −1 ). The plateau VE increase during unloaded cycling was positively correlated with VE values measured at the ventilatory threshold and VO2 max. Measurement of ventilation during unloaded cycling may serve to predict the ventilatory performance of COPD patients and overweight subjects during an exercise rehabilitation program.